Hallmarks of primary neurulation are conserved in the zebrafish forebrain - Jonathan M. Werner (Nature Portfolio, 2021)
Jonathan Werner, Maraki Negesse et al. visualize zebrafish neurulation during development to determine whether hallmarks of neural tube formation in other vertebrates also apply to zebrafish. They find that neural tube formation in the forebrain shares features such as hingepoints and neural folds with other vertebrates, demonstrating the strength of the zebrafish model for understanding human neurulation.